2018
DOI: 10.1002/ep.12942
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of porous ceramics prepared from sandblasting waste and waste diatomite by co‐sintering process

Abstract: The purpose of this research is to recycle sandblasting waste from the surface treatment process of solar cell industry to replace waste diatomite (with a replacement ratio of 0–20%) to make water‐retention porous ceramics, and adopts the method of molding by semi‐dry pressing under a pressure of 5 MPa, as the heating temperature fluctuated between 1000, 1100, 1200, and 1270°C. With a heating rate of 5°C/min, the heating process continued for 120 minutes. The sintered samples were then examined to determine wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
4
2
1
Order By: Relevance
“…When the starch content increased from 0 wt.% to 40 wt.%, the apparent porosity increased from 46.54 wt.% to 59.28 wt.%. These findings are consistent with those of other authors, as reported in their studies [6,13,29]. This is corroborated by analyzing the SEM microphotographs in Figure 6.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…When the starch content increased from 0 wt.% to 40 wt.%, the apparent porosity increased from 46.54 wt.% to 59.28 wt.%. These findings are consistent with those of other authors, as reported in their studies [6,13,29]. This is corroborated by analyzing the SEM microphotographs in Figure 6.…”
Section: Discussionsupporting
confidence: 93%
“…When the starch content increased from 0 wt.% to 40 wt.%, the water absorption increased from 36.35 wt.% to 59.35 wt.%. These results are slightly lower than those obtained by Ho et al [29].…”
Section: Discussioncontrasting
confidence: 68%
“…Samples T 3 and P 1 had the lowest and highest thermal conductivity values of 0.09 and 0.62 W/(m.K), respectively. This was in agreement with Ho et al [39] that an inverse relationship exists between the thermal conductivity coefficient and porosity of the porous ceramics. The decreasing values of thermal conductivity corresponded with increasing values of water absorption as well as increasing apparent porosity in each case.…”
Section: A) B) C)supporting
confidence: 93%
“…(Wu and Zhang, 2019). It also serves as raw material for constructional heat-insulating and soundproof materials (Fraine et al, 2019) and additives to some types of cement, as well as a polisher (in the paste composition) for metals and marbles (Ho et al, 2019;Jiang et al, 2019). The diatomite-based ceramics is also used for heat insulation when producing aluminum (Li and Shi, 2019).…”
Section: Introductionmentioning
confidence: 99%